Artificial Intelligence in Procurement : Leveraging Google Gemini to Improve the Purchasing Process - Kastari, Lassi Pekka (My University, 2025)
This study explores the application of Google Gemini AI within the technical services purchasing process at a case company. The procurement department at the case company has identified a growing need to explore and implement AI-driven solutions to improve the efficiency and quality of its operations. While a growing body of literature demonstrates the potential of AI to enhance various facets of the purchasing process, research in this area is still developing. This research employs a design research approach, integrating Lean Six Sigma methodology, and uses data collected through observations, documentation, and workshops. The analysis includes lead time and defect measurements from five runs for each pilot case, comparing old and new process designs. Findings indicate that Google Gemini can reduce lead times for PO text and RFQ text generation; however, it also introduces challenges, including difficulties in adhering to templates and ensuring output consistency. The study reveals that while AI offers potential for efficiency gains in procurement, current limitations necessitate careful consideration of its implementation and continued development.

Tämä tutkimus tarkastelee Google Gemini tekoälyn soveltamista teknisten palveluiden ostoprosessissa eräässä case-yrityksessä. Yrityksen hankintaosasto on tunnistanut kasvavan tarpeen tutkia ja ottaa käyttöön tekoäly-pohjaisia ratkaisuja toimintojensa tehokkuuden ja laadun parantamiseksi. Vaikka kasvava määrä kirjallisuutta osoittaa tekoälyn potentiaalin parantaa hankintaprosessin eri osa-alueita, tutkimus tällä alueella on vielä kehittymässä. Tämä tutkimus käyttää design research -lähestymistapaa, jossa yhdistetään Lean Six Sigma -metodologia, ja siinä hyödynnetään havaintojen, dokumentaation ja työpajojen avulla kerättyä dataa. Analyysi sisältää läpimenoajan ja vikojen mittaukset viidestä ajosta kullekin pilottitapaukselle, vertaillen vanhoja ja uusia prosessimalleja. Tulokset osoittavat, että Google Gemini voi lyhentää ostotilaustekstin ja tarjouspyyntötekstin luontiin kuluvaa aikaa; samalla siinä on kuitenkin haasteita, kuten mallipohjien noudattamisessa ja tuotoksen yhdenmukaisuuden varmistamisessa. Tutkimus osoittaa, että vaikka tekoäly tarjoaa potentiaalia tehostaa hankintoja, nykyiset rajoitukset edellyttävät huolellista harkintaa sen käyttöönotossa ja jatkuvaa kehitystä.
Keywords: artificial intelligence; purchasing; lean thinking; processes; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management